2021
DOI: 10.1021/acsami.1c01791
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Acid-Responsive Properties of a Highly Porous Vinylene-Linked Covalent Organic Framework

Abstract: The recently emerging vinylene-linked covalent organic frameworks (VCOFs) stand out from other COFs with exceptional chemical stability and favorable light-emitting properties, promising sensing applications for acids/bases or in strong acidic/basic conditions. Here we systematically investigated the reversible color and fluorescent response of a VCOF functionalized with pyridyl groups to acids/pH. The COF was synthesized with a record surface area for VCOFs and shows reversible hydrochromic and acidochromic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“… 8 Several studies report on COF-based chemosensors for the detection of gaseous hydrochloric acid, 25,26 and a series of aqueous Brønsted acids. 26,27 Recently, Yang et al have studied the effect of imine-protonation on the optical properties of three imine-linked COFs. It was found that all COFs showed a bathochromic shift after acid exposure due to the protonation of the imine bond.…”
Section: Resultsmentioning
confidence: 99%
“… 8 Several studies report on COF-based chemosensors for the detection of gaseous hydrochloric acid, 25,26 and a series of aqueous Brønsted acids. 26,27 Recently, Yang et al have studied the effect of imine-protonation on the optical properties of three imine-linked COFs. It was found that all COFs showed a bathochromic shift after acid exposure due to the protonation of the imine bond.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, to achieve ideal metallaphotoredox catalytic activities, [2,2′-bipyridine]-5,5′-dicarbaldehyde, possessing two suitable metal coordination sites and long π conjugated 4,4′,4′′,4′′′-(1,9-dihydropyrene-1,3,6,8-tetrayl)tetraaniline were chosen to assemble the organic backbone of the MCOF. Although similar frameworks 20 have previously been reported, and several pioneering studies on utilizing them to coordinate transition metals for classical cross couplings 21 have been developed, the introduction of cobalt onto it towards uncovering new photo reactivities for visible-light-driven C–H annulation is still the first attempt.…”
Section: Resultsmentioning
confidence: 98%
“…Others such as OTA‐intrinsic fluorescence and fluorescent polymer dots in Table 3 are not specifically described herein because these fluorescent probes are rarely used in mycotoxin fluorescent aptasensors. In addition, metal–organic frameworks (MOFs) and covalent–organic frameworks (COFs) show outstanding fluorescent properties, which can be used as fluorescent probes for sensing (Bu et al., 2021; Yang et al., 2021). However, there are few reports of applying MOFs or COFs as fluorescent probes to prepare fluorescent aptasensors for mycotoxin detection.…”
Section: Constituted Elements Of Fluorescent Aptasensorsmentioning
confidence: 99%